2015
DOI: 10.1111/ajt.13386
|View full text |Cite
|
Sign up to set email alerts
|

High Risk of Graft Failure in Emerging Adult Heart Transplant Recipients

Abstract: Emerging adulthood (17-24 years) is a period of high risk for graft failure in kidney transplant. Whether a similar association exists in heart transplant recipients is unknown. We sought to estimate the relative hazards of graft failure at different current ages, compared with patients between 20 and 24 years old. We evaluated 11 473 patients recorded in the Scientific Registry of Transplant Recipients who received a first transplant at <40 years old and had at least 6 months of graft function. Timedependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 52 publications
1
29
0
Order By: Relevance
“…Yet, a regression analysis demonstrated that an increase in age is associated with a decrease in the probability of overall treatment adherence. These findings are consistent with previously published studies . Specifically, Shamaskin et al.…”
Section: Discussionsupporting
confidence: 94%
“…Yet, a regression analysis demonstrated that an increase in age is associated with a decrease in the probability of overall treatment adherence. These findings are consistent with previously published studies . Specifically, Shamaskin et al.…”
Section: Discussionsupporting
confidence: 94%
“…Although the high‐risk window has been identified in other solid organ transplant recipients, the effect is not seen in all organs. Adolescent and young adult heart transplant recipients have an increased rate of graft failure during the ages 17–24 years, however liver transplant recipients do not . Patients with cystic fibrosis who receive a lung transplant have a higher risk of death during this period …”
Section: Discussionmentioning
confidence: 99%
“…The impact of adolescence and its transitions are supported by evidence from Foster et al who showed that the incidence of graft failure in renal, heart and liver transplant recipients peaks between 17 and 21 years of age, regardless of age of transplant. [4][5][6]18 This may be the basis of the poorest outcomes noted in the 15-19-year cohort. Unlike those transplanted in childhood (o10 years), who will have a prolonged period of sustained stability before entering the "high-risk" period, 15-19-year-old recipients enter this "high-risk" period at the time of transplant.…”
Section: Discussionmentioning
confidence: 99%
“…younger recipients, with higher rates of acute and chronic rejection, graft loss and mortality. [1][2][3][4][5][6] The reasons for these poorer outcomes remain undefined and they occur despite the adolescent recipients' young age and relative lack of comorbidities. Adolescence is a period fraught with inherent challenges in both chronically ill and healthy individuals.…”
mentioning
confidence: 99%